What You Don't Notice Can Harm You: Age-Related Differences in Detecting Concurrent Visual, Auditory, and Tactile Cues. (June 2018) - Pitts, Brandon J.; Sarter, Nadine
Objective: This research sought to determine whether people can perceive and process three nonredundant (and unrelated) signals in vision, hearing, and touch at the same time and how aging and concurrent task demands affect this ability. Background: Multimodal displays have been shown to improve multitasking and attention management; however, their potential limitations are not well understood. The majority of studies on multimodal information presentation have focused on the processing of only two concurrent and, most often, redundant cues by younger participants. Method: Two experiments were conducted in which younger and older adults detected and responded to a series of singles, pairs, and triplets of visual, auditory, and tactile cues in the absence (Experiment 1) and presence (Experiment 2) of an ongoing simulated driving task. Detection rates, response times, and driving task performance were measured. Results: Compared to younger participants, older adults showed longer response times and higher error rates in response to cues/cue combinations. Older participants often missed the tactile cue when three cues were combined. They sometimes falsely reported the presence of a visual cue when presented with a pair of auditory and tactile signals. Driving performance suffered most in the presence of cue triplets. Conclusion: People are more likely to miss information if more than two concurrent nonredundant signals are presented to different sensory channels. Application: The findings from this work help inform the design of multimodal displays and ensure their usefulness across different age groups and in various application domains.